Animal welfare standards in red deer (Cervus elaphus) farming - Miroslav I. Urošević; Bruno Esattore; Laura Saggiomo; Zoran A. Ristić; Nenad Stojanac (Archives of Veterinary Medicine, 2019)
In the last decades, significant interest of consumers in game meat and products has reflected in the worldwide development of wild animal farming. Among the different farmed species, the Red deer (Cervus elaphus) takes an important place, being farmed in several different countries around the world and in most countries within the European Union. In this regard, the European Union has promulgated laws and regulations aimed at defining and organizing this business as well as ensuring the welfare of the animals. So far, relevant data on this topic are not available in Serbia probably due to the lack of deer farms across the country. In this paper, we will review the major issues related to Red deer keeping (i.e., housing, feeding and watering practices, management and handling, transport and velvet harvest) and give the proposals as a basic guideline principles for future Red deer farming in Serbia.